THE COLOURS IN LITHUANIAN AND FRENCH PROVERBS - Kosova, Svetlana; Klanauskaitė, Paula (Verbum, 2015)
The aim of the article is a comparison of Lithuanian and French proverbs by choosing the names of colours as the main aspect. This is to some extent a new way of analysing proverbs with colour as the key word. Seven main aspects of proverbs are mentioned in the article supported by an analysis and comparison of proverbs in both languages. Two different dictionaries have been used for the research: K. Grigas, L. Kudirkienė, R. Kašetienė, G. Radvilas ir D. Zaikauskienė Lietuvių Patarlės ir Priežodžiai and M. Maloux LAROUSSE Dictionnaire des proverbes sentences et maximes. It is clearly seen from the examples that colours may have various shades, which is illustrated by presenting the names of colours and their codes, as well as by translating French proverbs into the Lithuanian language. In addition, the meaning of colours as symbols is explained comprehensively and it is noted that the real meaning of a colour in a proverb can be interpreted freely, since it does not have one unequivocal meaning. The modern usage of French and Lithuanian proverbs is not a common phenomenon; it is considered that proverbs are more a part of the folklore. However, it is emphasised that proverbs are historic and cultural heritage of a nation and show its individuality and relations with other cultures. While studying the proverbs, it has been noticed that a list of the colours mentioned in the proverbs of both languages could be longer or more comprehensive. However, it is observed that the most common colours used in proverbs are black, white, green, red, blue and brown, thus the greatest attention was given to those colours in particular. Examination of the meaning of those colours in proverbs revealed traces of commonness of both languages. Despite the lexical, historic or cultural differences of both languages, the meaning of colours is the same, for example, in both languages black colour means bad, dishonest things and, on the contrary, white colour means beauty and goodness. Presumably, this is because people, even though they speak in different languages, are likely to experience similar associations when looking at the same colours.